Evolution of Media in China: From Traditional News Outlets to New Media - Xu W. (Strategies of Sustainable Development: Social, Law and External-economic Aspects, 2024)
this article explores the transformation of China's media landscape, highlighting the shift from traditional news outlets to the emergence of new media platforms. Historically, news dissemination in China was dominated by state-controlled media organizations, limiting public participation and freedom of expression. However, with the advent of the internet, social media, and online news portals, the Chinese population now has unprecedented access to information and the ability to engage in public discourse. The rapid growth of social media platforms and the rise of online news portals have challenged the traditional notion of news reporting and provided more diverse perspectives. Nonetheless, the government's censorship efforts and control of content raise concerns about freedom of expression. This article concludes by discussing the challenges and opportunities presented by the evolution of media in China.
Keywords: Китай; социальные сети; государственный контроль; China; social media; медиа-ландшафт; традиционнве новостные издания; государственные медиаорганизации; новостные порталы; гражданская журналистика; цензура; свобода выражения; media landscape; traditional news outlets; new media platforms; state-controlled media; online news portals; citizen journalism; censorship; freedom of expression; government control